Mexico's indigenous communities: their lands and histories, 1500-2010 - Ruiz Medrano, Ethelia, author; Davidson, Russ, translator; University Press of Colorado, publisher (Colorado State University. Libraries, 2010)
Presenting an account of indigenous history in central and southern Mexico from the sixteenth to the twenty-first centuries, this title destroys the notion that Indians were victims of forces beyond their control and have little connection with their ancient past.
Historical background: Indian access to colonial justice in the sixteenth century -- Indigenous negotiation to preserve land, history, titles, and maps: seventeenth and eighteenth centuries -- Indigenous negotiation to preserve land, history, titles, and maps: nineteenth and twentieth centuries -- Defending land: Indian pueblo's contemporary quest for the origins of local community history.
Keywords: Indians of Mexico -- Land tenure -- History; Indians of Mexico -- Legal status, laws, etc. -- History; Indians of Mexico -- Claims; Indians of Mexico -- Ethnic identity; Land tenure -- Law and legislation -- Mexico -- History; Ethnohistory -- Mexico